Stakeholders’ awareness and acceptance of the vision, mission, goals, and outcomes statements of a teacher education college - Januard D. Dagdag; Noel A. Palapuz; Jane C. Caliboso; Eddie I. Peru; Regina P. Mauro (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study examined the awareness and acceptance of the stakeholders of a teacher education college in the Philippines of their university vision and mission and the college goals, and outcomes statements (VMGOs). Of the 700 target respondents, 406 stakeholders responded to the survey transcribed in Google Form. They were 42 school personnel, 106 parents, and 258 students; 301 females and 105 males. The five-point rating scales asked the respondents to assess their awareness and acceptance of 16 statements including one vision, one mission, five institutional outcomes (IO), two college goals, and seven program outcomes (PO). The respondents as a whole indicated they were very aware of the VMGOs and these were very acceptable for them. However, the school personnel were consistently more aware than the students and the parents/officials; while the parents/officials consistently indicated the lowest awareness and acceptability scores for all the statements. The results further revealed a significant acceptable relationship between awareness and acceptability scores. The variables share a variance ranging from 51% to 61% confirming that as awareness increases, acceptance rate also increases. Various implications of these findings are discussed.